Terminology and Translation — bringing research and professional training together through technology - Maia, Belinda (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractAs terminology has become more descriptive than prescriptive in theory and practice, translation of special domain language has become more professional, and these processes have been accelerated by the possibilities offered by information technology. This paper will describe our online suite of tools for special domain corpora compilation and analysis, term extraction and term database management, Corpógrafo, which has been developed by computer engineers in close cooperation between the teachers and students of a Master’s degree in Terminology and Translation. Special emphasis will be given to its implications for teaching and research.